Labour market integration of immigrants in Portugal in times of austerity: resilience, in situ responses and re-emigration - Esteves, Alina (2017)
The austerity regime implemented in Portugal to face the financial and economic crisis caused readjustments in the country’s productive structure and labour market with an impact on immigrants’ lifeworlds. This article aims at analysing the consequences of the crisis in the lives of third-country nationals living in Portugal, reflecting particularly on the impact on their integration process, understood as economic incorporation, in a context of increasing work precariousness. Special attention will be given to the resilience of immigrants visible in their responses to the labour market constraints, namely through their choices of geographic (im)mobility and also the implementation of strategies to ‘normalise’ their lives. Starting with a brief reference to the meaning of integration in Portugal in a context of crisis, we draw on data from two research projects, arguing that despite the increased hardship, the resilience of foreign workers is considerable and they still think it is worth coming to Portugal. The strategies adopted may be either in situ or implying onward migration, resulting from the combination of context opportunities and individual agency. Factors like legal status, education and having relatives abroad play a moderate role in this process.